2012
DOI: 10.1117/12.911351
|View full text |Cite
|
Sign up to set email alerts
|

New head equivalent phantom for task and image performance evaluation representative for neurovascular procedures occurring in the Circle of Willis

Abstract: Phantom equivalents of different human anatomical parts are routinely used for imaging system evaluation or dose calculations. The various recommendations on the generic phantom structure given by organizations such as the AAPM, are not always accurate when evaluating a very specific task. When we compared the AAPM head phantom containing 3 mm of aluminum to actual neuro-endovascular image guided interventions (neuro-EIGI) occurring in the Circle of Willis, we found that the system automatic exposure rate cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…For this experiment, a head phantom is used that consists of 2.5 cm acrylic + 7 mm Al + 10 cm acrylic + 6 mm Al + 2.5 cm of acrylic and was constructed using NEMA phantom blocks (Figure 7). This more closely approximates the head attenuation experienced during anterior-posterior imaging in neuro-EIGI clinical MAF tests [10] . With this phantom attenuating the x-ray beam, exposures to the object and detectors are expected to closely represent the actual x-ray beams experienced in frontal neuro-EIGIs in this task dependent metric.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…For this experiment, a head phantom is used that consists of 2.5 cm acrylic + 7 mm Al + 10 cm acrylic + 6 mm Al + 2.5 cm of acrylic and was constructed using NEMA phantom blocks (Figure 7). This more closely approximates the head attenuation experienced during anterior-posterior imaging in neuro-EIGI clinical MAF tests [10] . With this phantom attenuating the x-ray beam, exposures to the object and detectors are expected to closely represent the actual x-ray beams experienced in frontal neuro-EIGIs in this task dependent metric.…”
Section: Methodsmentioning
confidence: 67%
“…In order to simulate the attenuation of x-rays by a patient in neuro-EIGIs, a custom phantom is used with the test objects to mimic the attenuation of x-rays by a human head. While the ANSI/AAPM head phantom has been recommended for lateral projections [2.5 cm acrylic + 2 mm Al + 10 cm acrylic + 1 mm Al + 2.5 cm of acrylic (Figure 6)] [9] , it has been reported that this phantom is not suitable for measurements involving frontal skull imaging as used in most neuro-EIGI procedures [10] . For this experiment, a head phantom is used that consists of 2.5 cm acrylic + 7 mm Al + 10 cm acrylic + 6 mm Al + 2.5 cm of acrylic and was constructed using NEMA phantom blocks (Figure 7).…”
Section: Methodsmentioning
confidence: 99%
“…so that the grid can be placed perfectly and rigidly beneath the high resolution CMOS detector 6 . In this study, we used a stationary Smit Röntgen X-ray detector grid with a high resolution Dexela 1207 CMOS X-ray detector (pixel size 75 μm and sensitivity area 11.5cm × 6.5cm) to image the simulated artery block phantom (Nuclear Associates, Stenosis/Aneurysm Artery Block 76-705) with the frontal head equivalent phantom 7,8 used as the scattering source. The artery phantom contained three iodine-filled simulated arteries of widths and depths 1, 2 and 4 mm in one half of the block and the other half of the block had no features (Fig 2a).…”
Section: Methodsmentioning
confidence: 99%
“…The study was done by analyzing images of the simulated artery block phantom (Nuclear Associates, Stenosis/Aneurysm Artery Block 76-705) taken with the frontal head equivalent phantom 5, 6 used as the scattering source. The artery phantom was an acrylic block (15 × 45 × 2.5 cm thick) that contained three iodine-filled simulated arteries whose widths were 1, 2 and 4 mm in one half of the block while the other half has no features (see Fig.…”
Section: Methodsmentioning
confidence: 99%